Electromigration failure induced by interdiffusion between Al trace and Cu seed layer in the immortal microbump in three-dimensional integrated circuit - Yifan Yao; Yuxuan An; K.N. Tu; Yingxia Liu (Journal of Materials Research and Technology)
Owing to ultrahigh current density and severe Joule heating, electromigration (EM) in the microbump is a crucial reliability issue in three-dimensional integrated circuit. In this study, we investigated a novel EM weak link in our 13 μm microbump after all of the solder transformed into intermetallic compound (IMC). Under the test condition of 132 °C and 1.57 × 105 A/cm2, there was not any sign of failure of the microbump sample until 4100 h, and we proved that the microbump had already transformed into a full-IMC structure much earlier. The current density was then doubled at 4100 h and the EM condition turned into 164 °C and 3.14 × 105 A/cm2. In this case, we detected a semi-failure at 5000 h from the resistance curve of the sample and observed the interdiffusion between Al trace and Cu seed layer in the microbump, accompanied by Al4Cu9 IMC formation. A crack also formed at the Cu/Al interface due to the tensile stress induced by the volume shrinkage of 4.43 % during the Al4Cu9 IMC formation process. The interdiffusion was attributed to the breakdown of the Ti barrier layer between the Al trace and Cu seed layer. When the current stress was continuously applied, a burn-out open circuit and catastrophic failure occurred in the circuit. Finally, a schematic diagram describing the EM failure evolution in the microbump with a full-IMC structure was provided.